Impact of COVID-19 on mortality in out-of-hospital cardiac arrest patients with return of spontaneous circulation: a retrospective cohort study - Nai-Chen Shih; Han-Wei Yeh; Shun-Fa Yang; Yu-Hsun Wang; Chung-Hsien Chaou; Chao-Bin Yeh (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background This study aims to compare the mortality rates of OHCA patients with and without COVID-19 infection across different follow-up periods and explores the factors may play a significant role in determining OHCA outcomes. Methods This study utilized data from the US Collaborative Network in TriNetX. A total of 25,271 hospitalized OHCA patients were recruited from records spanning from January 1, 2020, to December 31, 2023. Study population divided into two groups, COVID-19 positive and COVID-19 negative groups. The mortality risk of the two groups was observed based on different follow-up periods. Subgroup analyses on sex, age, antivirals use, COVID-19 virus variant epidemic period were also conducted. Results Our study included 2,776 patients in each group (COVID vs. non-COVID). The primary outcome was mortality at 14-day and 90-day follow-ups. COVID-19 patients had a lower 14-day mortality (HR 0.82, 95% CI: 0.76–0.88) but higher 90-day mortality (HR 1.16, 95% CI: 1.09–1.24) compared to non-COVID-19 patients. Secondary outcomes included higher mortality in COVID-19 patients under 65, and this trend persisted in those aged 65 and over. Male COVID-19 patients had elevated mortality risk. The Alpha and Delta variant period showed a higher mortality rate for COVID-19 patients than non-COVID-19 patients. Conclusion COVID-19 was associated with a higher risk of mortality in OHCA patients.